T. Emerson collection - Emerson, T.
Volumes containing a compilation of biographical references concerning various westerners involved in the siege of Peking (1900) during the Boxer uprising in China, gathered by Emerson, a newspaperman (?).
Newspaperman.
Collection material in English, with French.
Keywords: Beijing (China); China -- History -- Boxer Rebellion, 1899-1901.; Newspapermen